APTRA‐Based Luminescent Lanthanide Complexes Displaying Enhanced Selectivity for Mg2+. Issue 30 (3rd May 2018) - Walter, Edward R. H.; Williams, J. A. Gareth; Parker, David
Abstract: A series of three europium(III) complexes has been created in which an APTRA moiety has been integrated into the sensitising chromophore (APTRA= o ‐aminophenol‐ N, N, N ‐triacetate). The constitutionally isomeric complexes EuL 1 and EuL 2 feature the APTRA unit linked to a metal‐bound pyridine ring through an alkynyl unit, differing according to the disposition of the APTRA substituents relative to the C≡C unit ( para ‐N and para ‐O). In EuL 3, the APTRA ring is directly bonded to the Eu‐coordinated pyridine ( para ‐O). The metal binding affinities for magnesium, calcium and zinc ions have been measured by using emission and excitation spectroscopy. The pyridylalkynylaryl systems, EuL 1 and EuL 2, offer superior affinity and selectivity for Mg 2+ . The Mg 2+ affinities are surprisingly very different from prior studies on structurally related systems that incorporate organic fluorophores as reporters, as opposed to the macrocyclic Eu complex moiety. A much‐reduced affinity for calcium and zinc—possibly arising from the lower donor ability of the aryl N or O atoms arising from extended conjugation—means that magnesium ion concentrations can be measured directly in serum for the first time, by using such an approach. An apparent dissociation constant for magnesium binding of K d =2.4 mm was calculated in the serum background. Abstract : Sensing Mg 2+ in serum : o ‐Aminophenol‐ N, N, N ‐triacetate (APTRA) is a well‐known ligand for Group 2 metal ions, with higher relative affinity for Mg 2+ over Ca 2+ than related ligands like EDTA. Yet, its Ca 2+ affinity is too high to permit Mg 2+ sensing under normal biological conditions. Here, europium(III) complexes featuring a pendent APTRA linked through a pyridylalkynyl or pyridylaryl unit have been prepared; they respond to M 2+ binding through modulation of the Eu 3+ luminescence intensity. The former shows unexpectedly reduced affinity for Ca 2+, allowing [Mg 2+ ] to be monitored in serum.